Influence of the Diffusion Media Structure for the Bubble Distribution in Direct Formic Acid Fuel Cells. Issue 13 (14th September 2020) - Watanabe, Konosuke; Araki, Takuto; Tsujiguchi, Takuya; Inoue, Gen
Abstract : Direct formic acid fuel cells (DFAFCs) have received considerable attention because they can generate a higher power density compared to other direct liquid fuel cells. However, when generated CO2 bubbles are retained in the anode's porous transport layer (PTL), the performance of the DFAFCs deteriorates. The gas–liquid two-phase flow behavior within a PTL is not clear; therefore, in this work the power-generation characteristics of DFAFCs using two types of PTL, carbon paper and carbon cloth, were investigated. It was found that the maximum current density was approximately 60 mA cm −2 higher with the carbon cloth than with the carbon paper. The CO2 bubble distribution in the anode's PTLs was visualized by X-ray computed tomography and discuss the effects of the bubbles on the power-generation performance of DFAFCs. We found that interstices in a carbon-cloth PTL provided pathways for bubble migration and release to the channel, so that the bubbles did not deteriorate the power output. Bubble accumulation in a carbon-paper PTL led to a drop in power output, confirming that the structure of the PTL and the CO2 bubbles affect the power-generation characteristics.